Don't Think - Burgin, Richard (Book collections on Project MUSE., 2016)
Five-time Pushcart Prize winner Richard Burgin's stories have been praised by the New York Times Book Review as "eerily funny, dexterous, and too haunting to be easily forgotten," with "characters of such variety that no generalizations about them can apply." In Don't Think, his ninth collection of short fiction, Burgin offers us his most daring and imaginatively varied work to date. The stories explore universal themes of love, family, and time, examining relationships and memory--both often troubled, fragmented, and pieced back together only when shared between characters. 7v6In the title story, written in propulsive, musical prose, a divorced father struggles to cling to reality through his searing love for his highly imaginative son, who has been diagnosed with Asperger's syndrome. In "Of Course He Wanted to Be Remembered," two young women meet to commemorate the death of a former college professor with whom they were both unusually close--though in very different ways. In "V.I.N.," a charismatic drug dealer tries to gain control of a bizarre cult devoted to rethinking life's meaning in relation to infinite time, while in "The Intruder," an elderly art dealer befriends a homeless young woman who has been sleeping in his basement. Together, the nine stories in Don't Think illuminate the astonishing fact of existence itself while justifying the Philadelphia Inquirer's assessment that Burgin is one of America's most distinctive storytellers.